Effect of Applying the E-Learning Learning Model as a Solution to the Covid-19 Pandemic on Student Learning Outcomes - Jainal Abidin; Agustina Siburian (MultiTech Publisher, 2023)
The process of development of science and technology in this era is growing rapidly. This is in line with the times, we are faced with a world problem, namely the COVID-19 pandemic which requires us to comply with health protocols and avoid crowds to reduce the process of spreading the covid-19 virus. The effect of implementing these regulations resulted in the teaching and learning process that should have been carried out face to face to become network-based learning. The use of E-learning media is expected to overcome learning limitations due to the covid-19 pandemic. So, when conducting research it was found that learning with E-learning media had not been able to provide satisfactory results on student learning outcomes, where student learning outcomes did not reach the target KKM value = 75. Many factors influenced this including not all students who have smartphones and low network signal quality.